Brajisalem: Biblical Cosmology, Power Dynamics and the Brazilian Political Imagination. Issue 5 (20th October 2021) - Shapiro, Matan
ABSTRACT: Based on fieldwork with Brazilian neo-Pentecostal pilgrims to the Holy Land and ongoing survey of social media in this article I argue that Brazilian neo-Pentecostals increasingly imagine Brazil as a Promised Land and the Brazilian People as the People of God. Here, different substances associated with the Holy Land, the Jewish People and Jesus Christ are used to disperse in Brazil divine power, which is seen to emanate from God. This imaginary seeks to replace the hegemony of the democratic ethos of power in Brazil, which is seen to emanate bottoms-up from the Brazilian People. I associate this process with the conservative wave sweeping through the Brazilian political system and show what a Brazilian political imagination whose spiritual and moral centre is located in Biblical Jerusalem may look like.